Joint ventures : ownership structure, accounting policy and information disclosure issues. - Lim, Chee Yeow. (2008)
This thesis examines factors that determine the firm's choice of joint venture ownership structure and economic incentives to equity account or consolidate joint ventures. It also examines impact of the disclosure of supplementary information of joint ventures on information asymmetry as measured by relative bid-ask spreads, trading volume and price variability.